European defence policy and subsidiarity: The imperative of the EU level. Issue 1 (April 2019) - Howorth, Jolyon
Since the Treaty of Westphalia in 1648, defence policy, across Europe, has traditionally been the preserve of the nation state. That remains the default situation today, despite over two decades of movement towards a common EU security and defence policy. European leaders, ever since the 1980s, have insisted that the EU level is the most appropriate for this policy area, and public opinion appears to agree with them. Yet, despite many developments in the direction of a 'European army', and despite the launch of dozens of EU overseas missions, defence planning and procurement, as well as the deployment of forces, remain the preserve of the EU's national governments. Since 2016 we have witnessed an intensification of the move towards the EU level. This article argues that it is still too soon to determine whether a genuine shift away from the nation-state level is now in progress.